Peta Dinamis 3 Dimensi pada Gedung Universitas Darussalam Gontor Berbasis Augmented Reality - Pradhana, Faisal Reza; Taufiqurrahman, Taufiqurrahman; Fauzan, Ady (Universitas Nusantara PGRI Kediri, 2021)
Darussalam Gontor University (Unida Gontor) is a campus with a fairly rapid development of infrastructure. The paper-based building prototype design belonging to UNIDA Gontor is considered not able to visually represent the building that has been or will be built. This research aims to provide a prototype design update using more modern and dynamic technology that can be seen from all sides of the building and does not require physical storage, also can be used anytime and anywhere.The Application content is taken through the visual data collection stage in the form of detailed photos of buildings taken through cameras and drones. This media is based on Android which uses marker based augmented reality technology to implement 3-dimensional visualization of campus building objects, which are created through the steps of the waterfall model. The test is carried out in two stages, namely the suitability of the application with various android devices which shows compatibility with devices with a minimum size of 5 inches. The second test was conducted by distributing questionnaires to the staff of the facilities and infrastructure division of Unida Gontor with an average score of 90%, and the lecturers and multimedia student group 89.52%.